Hubungan antara Manajemen Waktu dengan Prokrastinasi Akademik pada Siswa SMA di Kabupaten Rokan Hulu, Riau - Aggraini, Nirmala; Primanita, Rida Yanna (YASIN, 2025)
Academic procrastination is widely acknowledged as the postponement of assignment completion. This study seeks to explore the relationship between time management and academic procrastination among high school students in Rokan Hulu Regency, Riau. Utilizing a correlational quantitative methodology, the research surveyed 336 high school students selected through the One Stage Cluster Random Sampling technique. Data collection was conducted via both online questionnaires and paper-based survey forms. The analysis demonstrated a statistically significant negative correlation (r = -0.346, p < 0.001) between time management and academic procrastination among the participants. These findings suggest that effective time management strategies may mitigate the tendency for academic procrastination, underscoring the importance of fostering such skills in educational settings. The implications of this research are profound, indicating that enhancing time management abilities could lead to improved academic performance and overall student well-being. Future interventions aimed at promoting time management may significantly benefit high school students, thereby contributing to their academic success and reducing procrastination-related stress.< 0.001) between time management and academic procrastination among the participants. These findings indicate that effective time management strategies may alleviate the propensity for academic procrastination, thereby highlighting the critical importance of cultivating such skills within educational contexts. The implications of this research are substantial, suggesting that the enhancement of time management competencies could lead to improved academic performance and overall student well-being. Future interventions designed to promote time management may yield significant benefits for high school students, ultimately contributing to their academic success and reducing stress associated with procrastination.